2019
DOI: 10.1536/ihj.18-636
|View full text |Cite
|
Sign up to set email alerts
|

Multimode Computed-Tomography-Guided Thrombolysis under a Prolonged Time Window in Acute Ischemic Stroke Patients with Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is an independent risk factor for intracranial hemorrhage in patients receiving recombinant-tissue-type plasminogen activator (rt-PA) thrombolytic therapy. Research showed that patients with acute ischemic stroke (AIS) could benefit from multimode computed-tomography-(CT-) guided intravenous thrombolysis over 4.5 hours. The medical data of patients with AIS in our center were retrospectively reviewed, and the data of the multimode CT-guided thrombolytic therapy or nonthrombolytic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Heterogeneity existed in several statistical results in our study, for example, in mRS 0-1 at 90 days after stroke analysis, I 2 was 71.0%. By sensitivity analysis, heterogeneity was derived from two studies [14,15]. The causes of heterogeneity in these two studies were analyzed, one study [14] included more severe stroke (NIHSS > 10) patients, one study [14] included patients with a longer thrombolysis time window (3-9 h) than the others.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Heterogeneity existed in several statistical results in our study, for example, in mRS 0-1 at 90 days after stroke analysis, I 2 was 71.0%. By sensitivity analysis, heterogeneity was derived from two studies [14,15]. The causes of heterogeneity in these two studies were analyzed, one study [14] included more severe stroke (NIHSS > 10) patients, one study [14] included patients with a longer thrombolysis time window (3-9 h) than the others.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline characteristics of patients included in these studies were shown in Table 1 and Table 2. Eleven studies [6,8,10,[12][13][14][16][17][18][19]24] compared IVT-treated AF to non-AF patients, two studies [20][21] compared IVT-treated to non-IVT in AF patients, and five studies [5,7,9,11,15] included two kinds of comparative data mentioned above. Figure 2A).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations